Offset tracking procedure applied to high resolution SAR data on Viedma Glacier, Patagonian Andes, Argentina - Riveros, Natalia Cecilia (2013)
Main aim of this work is to explore the suitability of high resolution SAR images for measuring ice flow velocity within glaciers. Available techniques for this purpose are Differential SAR Interferometry (DInSAR) and Offset Tracking. The former, although theoretically much more precise, is frequently limited by coherence loss (or lacking of coherence) in glacier environment. The latter constitutes an alternative that works well when displacements are large. Study area is the Viedma Glacier (Santa Cruz, Argentina), one of the largest uncovered ice bodies in the South Patagonian Ice (SPI). High resolution COSMO-SkyMed (CSK) acquisitions were processed by estimating range and azimuth offset fields. Useful results, consisting in displacement maps showing areas with different fast-flowing units, were obtained by Offset Tracking processing.